2012
DOI: 10.1002/jclp.21906
|View full text |Cite
|
Sign up to set email alerts
|

Metacognition and Social Cognition in Schizophrenia: Stability and Relationship to Concurrent and Prospective Symptom Assessments

Abstract: Metacognitive deficits are a stable feature of schizophrenia related with negative symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
82
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(102 citation statements)
references
References 42 publications
15
82
0
5
Order By: Relevance
“…Resolving this issue is critical for delineating whether these constructs should be treated as independent or converging abilities when assessing their impact in schizophrenia. In terms of what is known regarding these relationships, previous studies have observed that neurocognition, social cognition, and metacognition demonstrate moderate correlations with one another, with r-values typically ranging from 0.2 to 0.4 (Hamm et al, 2012;Ventura et al, 2013). However, this indicates that each ability only accounts for approximately 5% to 15% of the variance in the other constructs.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Resolving this issue is critical for delineating whether these constructs should be treated as independent or converging abilities when assessing their impact in schizophrenia. In terms of what is known regarding these relationships, previous studies have observed that neurocognition, social cognition, and metacognition demonstrate moderate correlations with one another, with r-values typically ranging from 0.2 to 0.4 (Hamm et al, 2012;Ventura et al, 2013). However, this indicates that each ability only accounts for approximately 5% to 15% of the variance in the other constructs.…”
Section: Introductionmentioning
confidence: 83%
“…One area of contention is whether these three cognitive processes are discrete constructs, as each represents trait phenomena that require both lower-and higher-order abilities (Lysaker et al, 2011;Biedermann et al, 2012;Hamm et al, 2012;Ventura et al, 2013). Resolving this issue is critical for delineating whether these constructs should be treated as independent or converging abilities when assessing their impact in schizophrenia.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, metacognition has been described as a significant predictor of personal recovery (Lysaker and Dimaggio, 2014). In this regard, it is interesting to note that cognitive disorganization symptoms demonstrated inverse associations with metacognitive abilities (Hamm et al, 2012). Another neglected predictor of therapeutic alliance in this study may be depression.…”
Section: Limitations and Conclusionmentioning
confidence: 64%
“…The variability in time since onset of the disorder may influence this relationship. Even though Hamm et al (2012) found that metacognitive deficits are a stable feature of schizophrenia, people who have had longstanding therapy might score higher on the MAS-A scale due to the way they have learned to talk about themselves in therapy. Several methodological issues may play a role as well, which are discussed later as part of the study's limitations.…”
Section: Discussionmentioning
confidence: 87%